Copper toxicity response influences mesotrophic S ynechococcus community structure - Rhona K. Stuart; Randelle Bundy; Kristen Buck; Majid Ghassemain; Kathy Barbeau; Brian Palenik (Environmental Microbiology, 2017)
Summary Picocyanobacteria from the genus Synechococcus are ubiquitous in ocean waters. Their phylogenetic and genomic diversity suggests ecological niche differentiation, but the selective forces influencing this are not well defined. Marine picocyanobacteria are sensitive to Cu toxicity, so adaptations to this stress could represent a selective force within, and between, ‘species’, also known as clades. Here, we compared Cu stress responses in cultures and natural populations of marine Synechococcus from two co‐occurring major mesotrophic clades (I and IV). Using custom microarrays and proteomics to characterize expression responses to Cu in the lab and field, we found evidence for a general stress regulon in marine Synechococcus . However, the two clades also exhibited distinct responses to copper. The Clade I representative induced expression of genomic island genes in cultures and Southern California Bight populations, while the Clade IV representative downregulated Fe‐limitation proteins. Copper incubation experiments suggest that Clade IV populations may harbour stress‐tolerant subgroups, and thus fitness tradeoffs may govern Cu‐tolerant strain distributions. This work demonstrates that Synechococcus has distinct adaptive strategies to deal with Cu toxicity at both the clade and subclade level, implying that metal toxicity and stress response adaptations represent an important selective force for influencing diversity within marine Synechococcus populations.